P037 Transcranial static magnetic field stimulation-induced modulation of motor cortex excitability in Parkinson's disease. Issue 3 (March 2017) - Dileone, M.; Mateos, L. Mordillo; Carrasco-Lopez, M.C.; Segundo-Rodriguez, J.; López-Aristegu, N.; Alonso-Frech, F.; Catalan-Alonso, M.J.; Obeso, J.; Oliviero, A.; Foffani, G.
Abstract : Question: tSMS is a new non-pharmacological, low-cost, non-invasive brain stimulation (NIBS) technique that decreases cortical excitability in healthy subjects. The effects of tSMS in Parkinson's disease remain unknown. We designed this study to test the ability of transcranial static magnetic field stimulation (tSMS) to modulate motor cortex excitability in patients with Parkinson's disease. Methods: We performed a randomized double-blind sham-controlled cross-over study to assess cortical excitability before and immediately after tSMS (or sham) applied for 10 min to the motor cortex of patients with Parkinson's disease. Motor cortex excitability was quantified by the amplitude of motor evoked potentials (MEPs) elicited by single-pulse transcranial magnetic stimulation (TMS). In a separated single-blind experimental session we evaluated the effects of tSMS on SICI and SICF. Patients were studied both after overnight withdrawal of dopaminergic therapy (OFF) medication and after an acute dose of levodopa (ON). Results: tSMS significantly decreased MEP amplitudes compared to sham in patients OFF medication, but not ON medication. Furthermore, tSMS induced an increase in SICI and a reduction in SICF only in OFF condition. Conclusions: These results suggest a dopamine dependency of tSMS-induced cortical changes and encourage the application of tSMS for future clinical trials in patients with Parkinson's disease.